Replacing Conventional Fertilization with Organomineral Fertilizer in ‘Hass’ Avocado Trees Improves Chlorophyll Indices and Fruit Size: A Bootstrap Simulation Approach - Marllon F. S. dos Santos; Rodrigo J. Milan; Bruna M. Costa; Tatiana E. Cantuarias-Avilés; Idemauro A. R. de Lara; Simone R. da Silva (Applied Fruit Science, 2026)
Modern agriculture faces significant challenges related to the depletion of finite resources used in fertilizer production. In response to this situation, the market has been adapting by developing biofertilizers or organomineral fertilizers, which incorporate an organic fraction into their composition. These fertilizers provide nutrients more gradually, reducing leaching. Studies on this topic are scarce for avocado trees, whose global production has been increasing. For this reason, the present research aimed to compare conventional fertilization with organomineral fertilization in ‘Hass’ avocado trees. A total of 20 plants per treatment were used in a commercial orchard, with treatments providing the same amount of nutrients. Variables related to vegetative growth, gas exchange, and productive data were evaluated. Data analysis was performed using bootstrap simulations, a resampling technique with 10,000 simulations, which enabled the construction of confidence intervals for the variables being assessed, resulting in an experimental optimization. Although no significant differences were detected in overall yield, the organomineral treatment showed increases of up to 10% in chlorophyll levels, 17.69% in fruit weight, and 8.35% and 9.18% in fruit length and diameter, respectively, compared to the conventional treatment. The bootstrap technique proved effective for analyzing this type of experiment, confirming the benefits of replacing conventional fertilization with organomineral fertilization, which provides nutrients more efficiently and sustainably.